1995
DOI: 10.1177/002224299505900401
|View full text |Cite
|
Sign up to set email alerts
|

Entry Strategy and Long-Term Performance: Conceptualization and Empirical Examination

Abstract: A product entry strategy—the timing of entry, the magnitude of investment at entry, and the area of competitive emphasis at entry—affects long-term performance in the marketplace. The authors develop the Entry Strategy Performance Model (ESPM) and propose an encompassing framework for product entry strategy research. They empirically test a research model derived from the ESPM through an examination and replication in the microcomputer software market. The authors’ significant findings are that initial competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 28 publications
4
48
0
1
Order By: Relevance
“…Because our population model only includes constructs measured using reflective indicators, we cannot make any statement with respect to PLS performance in cases when formative measures predominate. In addition, we do not discuss reasons that may favor a particular method other than those that appear in For example, Green, Barclay, and Ryans (1995) investigate the impact of entry strategy on long-term performance in the business word processor and graphics markets, where only 39 and 44 companies entered the market in the analysis period. However, in such situations, researchers must pay particular attention to including a sufficient number of indicators per construct.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because our population model only includes constructs measured using reflective indicators, we cannot make any statement with respect to PLS performance in cases when formative measures predominate. In addition, we do not discuss reasons that may favor a particular method other than those that appear in For example, Green, Barclay, and Ryans (1995) investigate the impact of entry strategy on long-term performance in the business word processor and graphics markets, where only 39 and 44 companies entered the market in the analysis period. However, in such situations, researchers must pay particular attention to including a sufficient number of indicators per construct.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, because all block 4 variables are assumed to be linear combinations of their indicators, PLS does not suffer from improper solutions and factor indeterminacy, as sometimes occurs in the context of CBSEM (e.g., Bollen 1987;Chen et al 2001;Krijnen et al 1998). Fornell and Robinson (1983) Yes Yes Fornell, Robinson, and Wernerfelt (1985) Yes Mayo and Qualls (1987) Yes Yes Qualls (1988) Yes Yes Yes Zinkhan and Fornell (1989) Yes Yes Yes Fornell, Lorange, and Roos (1990) Yes Yes Barclay (1991) Yes Alpert, Kamins, and Graham (1992) Yes Fornell (1992) Yes Yes Graham, Mintu, and Rodgers (1994) Yes Yes Yes Green, Barclay, and Ryans (1995) Yes Yes Yes Fornell et al (1996) Yes Yes Smith and Barclay (1997) Yes Yes Dawes, Lee, and Dowling (1998) Yes Yes Sirohi, McLaughlin, and Wittink (1998) Yes Yes Yes Ahuja, Galletta, and Carley (2003) Yes Yes Yes Arnett, Leverie, and Meiers (2003) Yes Yes Yes Yes Vanhamme and Snelders (2003) Yes Yes White, Varadarajan, and Dacin (2003) Yes Yes Yes Anderson, Fornell, and Mazvancheryl (2004) Yes Yes Cotte and Wood (2004) Yes Dellande, Gilly, and Graham (2004) Yes Gray and Meister (2004) Yes Reinartz, Krafft, and Hoyer (2004) Yes Yes Grégoire and Fisher (2005) Yes Hennig- Thurau et al (2006) Yes Ulaga and Eggert (2006) Yes Yes Venkatesh and Agarwal (2006) Yes Yes Hennig-Thurau et al (2007) Yes Mitchell and Nault (2007) Yes McFarland et al (2008) Yes First, it seems that PLS has prompted increasing interest among researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the measurement scales of the studied concepts are satisfactory in terms of reliability, convergent validity, and discriminant validity. This conclusion is made with a note of caution on the scales having AVE falling between 0.40 and 0.50 (lower than the common threshold of 0.50), yet being still usable (Barclay, 1991;Green et al, 1995).…”
Section: Validity and Reliability Of Measuresmentioning
confidence: 87%
“…Seminal work by (Bain 1956) on entry barriers found that a firm should enter a market if the investment at entry is less than the value of expected post-entry profits. While the literature recognizes that many factors can influence these two major components (Gatignon, Weitz, and Bansal 1990;Green, Barclay, and Ryans 1995), the major focus of systematic investigation has been related to costs, such as scale economies, sunk costs, limit pricing, absolute cost advantages (opportunity costs, rents, experience-related costs, network economies, etc. ), product differentiation (cost to mimic an established incumbent, such as design, advertising, and marketing), and switching costs (Gilbert 1989).…”
Section: Literature Reviewmentioning
confidence: 99%